Etika Bermedia Sosial dalam Perspektif Al-Qur’an dan Hukum Negara di Era Revolusi Industri 4.0 dan Society 5.0 - Dila Alfiana Nur Haliza; Merita Dian Erina; Azizah Jumriani Nasrum; Isna Fitri Choirun Nisa (Jurnal Riset Agama, 2022)
This study aims to determine the ethics of social media based on the perspective of the Qur'an and state law in the era of the industrial revolution 4.0 and society 5.0. This study uses a qualitative approach through descriptive-analytical methods. The results and discussion of this study indicate that the ethics of social media in the perspective of the Qur'an and state law in the era of the industrial revolution 4.0 and society 5.0 can minimize the problems faced by social media users if understood and applied in life. This study concludes that the ethics of social media in the perspective of the Qur'an and state law in the era of the industrial revolution 4.0 and society 5.0 is indeed very necessary to control humans in social media.